2007
DOI: 10.1093/ndt/gfl688
|View full text |Cite
|
Sign up to set email alerts
|

Lack of specific binding of Shiga-like toxin (verocytotoxin) and non-specific interaction of Shiga-like toxin 2 antibody with human polymorphonuclear leucocytes

Abstract: PMN are not acting as transporter for Stx in the pathogenesis of HUS. The interaction of a Stx antibody with PMN from HUS patients is not specific as it can also be observed in patients after HD (possibly due to activation of the PMN). Therefore, binding of Stx antibody to PMN is not reliable as a diagnostic tool for HUS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…The effect of traces of LPS or Stx1 in AST-conditioned medium on PMN activation cannot be completely ruled out. However, it was demonstrated previously that even after PMN priming with LPS, TNF-␣, or IL-8, Stx fails to activate PMN (18,22). Moreover, the enhanced PMNmediated toxicity observed after the combined treatment (LPS and Stx1) compared to that of LPS alone supports the finding that the observed effects may be due to an AST-derived factor(s) (Fig.…”
Section: Vol 78 2010 Stx1-induced Effects On Lps-sensitized Astrocysupporting
confidence: 72%
“…The effect of traces of LPS or Stx1 in AST-conditioned medium on PMN activation cannot be completely ruled out. However, it was demonstrated previously that even after PMN priming with LPS, TNF-␣, or IL-8, Stx fails to activate PMN (18,22). Moreover, the enhanced PMNmediated toxicity observed after the combined treatment (LPS and Stx1) compared to that of LPS alone supports the finding that the observed effects may be due to an AST-derived factor(s) (Fig.…”
Section: Vol 78 2010 Stx1-induced Effects On Lps-sensitized Astrocysupporting
confidence: 72%
“…Furthermore, some authors have proposed that PMN might facilitate the systemic absorption of Stx2, which in turn would increase the risk of developing HUS [35]. In contrast, other studies have failed to detect direct binding of Stx2 to resting human PMN [36,37,38] or Stx2 bound to PMN in HUS patients [31,33,34]. However, our findings indicating that Stx2 increases the expression of activation markers, stimulates ROS production, and triggers NETosis support the notion that this toxin is able to directly activate PMN in culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few years later, some of these authors reversed their position because they found that the binding of Stx to PMN was not specific, and they interpreted their own previous results as artifacts (7). In the meantime, other authors claimed that the PMN/Stx interaction was of little biological significance and failed to reproduce the early observations (8,9).…”
Section: Hemolytic Uremic Syndrome (Hus)mentioning
confidence: 99%
“…It should be noted that the three different groups that gave positive (10 -13) or partially positive (15) results on this topic have purified Stx by single-step affinity chromatography. In contrast, the three groups that were unable to reproduce Stx binding to PMN obtained the toxins by multistep purification methods (7,8) or from commercial sources (7,9). The methods employed, although sound and well known, contain numerous steps and chromatographic runs, which might have caused the partial conformational change inhibiting the binding of Stx1 to PMN.…”
Section: Treatmentsmentioning
confidence: 99%